1987
DOI: 10.1111/j.1471-4159.1987.tb02876.x
|View full text |Cite
|
Sign up to set email alerts
|

Ion Dependence of Neurotransmitter Uptake: Inhibitory Effects of Ion Substitutes

Abstract: Several ions commonly used as substitutes for Na+ or Cl- were found to inhibit directly the high-affinity uptake of norepinephrine, dopamine, serotonin, and gamma-aminobutyric acid, but not glutamate or glutamine. When Na+ was partially replaced by any of several different cations or sucrose the uptake of all neurotransmitters studied except that of serotonin was reduced more than could be accounted for by just the inhibitory effect of the cation substitute. In contrast, when Cl- was partially replaced by any … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
21
2
1

Year Published

1989
1989
1999
1999

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 22 publications
(22 reference statements)
7
21
2
1
Order By: Relevance
“…Wall et al (1993) reported a different Cl 2 requirement for [ 125 I]RTI-55 and DA binding. However, they did not compare the change in binding affinities, and the effect of the substitute anion (SO 4 22 ) remains to be clarified (see Shank et al, 1987). The present observation of a differential NaCl sensitivity of several uptake blockers and substrates in binding to the DAT is not affected by the substitution issue, because substitutes were not used.…”
Section: Discussioncontrasting
confidence: 46%
“…Wall et al (1993) reported a different Cl 2 requirement for [ 125 I]RTI-55 and DA binding. However, they did not compare the change in binding affinities, and the effect of the substitute anion (SO 4 22 ) remains to be clarified (see Shank et al, 1987). The present observation of a differential NaCl sensitivity of several uptake blockers and substrates in binding to the DAT is not affected by the substitution issue, because substitutes were not used.…”
Section: Discussioncontrasting
confidence: 46%
“…This system is characterized by ligand specificity, Na+ and temperature dependence, antagonizability by known blockers (nortriptyline, imipramine, and desipramine), and saturable and high-affinity uptake kinetics. In particular, the Km and Vma values are well within the range of such parameters measured for 5-HT-uptake systems in the central nervous system and blood platelets (6)(7)(8)(9)(10)(11)(12)(13).…”
Section: Discussionsupporting
confidence: 67%
“…Although the physiology and pharmacology of a number of neurotransmitter transport systems including that for serotonin have been extensively studied (6)(7)(8)(9)(10)(11)(12)(13), little is known about the biochemistry and molecular biology of any of these systems. With the hope of attaining such information, we report here the use of gene transfer (14)(15)(16)(17) in the establishment and identification of a clonal mouse fibroblast cell line, L-S1, that stably expresses a presumptively human highaffinity uptake system for serotonin (5-HT).…”
mentioning
confidence: 99%
“…In studies of the ion dependencies of dopamine transport, Na ϩ was substituted with choline and Clwith isethionate (Holz and Coyle, 1974;Shank et al, 1987;Kreuger, 1990;McElvain and Schenk, 1992;Povlock and Schenk, 1997). The resulting initial velocities were analyzed as described above, and in some experiments the effects of cocaine on the ion dependencies were investigated.…”
Section: Experimental Setup and Measurement Of Dopamine Transportmentioning
confidence: 99%